The Entrepreneurial Capacity of Young Farmers on Agribusiness Activities in West Java - Oeng Anwarudin; Sumardjo Sumardjo; Arif Satria; Anna Fatchiya (Jurnal Penyuluhan, 2020)
Farmer regeneration is a solution to the declining number of farmers. The research aims to analyze descriptively agribusiness activities, entrepreneurial capacity, the role of agricultural extension workers, government support, family, community, market and characteristics, and analyze the factors that influence the entrepreneurial capacity and agribusiness activities of young farmers. Data collection through interviews using research instruments. The instrument was in the form of a valid and reliable questionnaire. Data analysis was performed descriptively and inferentially using Structural Equation Models (SEM). The results found that young farmers had a better education than adult farmers, most of whom had not yet received training and apprenticeships, had access to Information and Communication Technology (ICT), perceptions of agricultural businesses were in the medium category but the motivation was still low. Likewise, young farmers receive external support, the role of agricultural extension workers is still low and has the capacity and agribusiness activities in the low category. Developing entrepreneurial capacity can be done by strengthening the characteristics of young farmers and the role of agricultural extension workers. The characteristics of young farmers are reflected through formal education, access to ICT, perception, and motivation. The role of the agricultural instructor is reflected as a facilitator, communicator, motivator, and consultant. Strengthening the agribusiness activities of young farmers can be done through their entrepreneurial capacity by increasing the ability of adaptation, leadership, ability to manage businesses, cooperation, and the role of agricultural extension workers as facilitators, communicators, motivators, and consultants. Agribusiness activities of young farmers can also be increased by strengthening external support including support from government, families, communities, and markets.